AN ERROR ANALYSIS ON STUDENTS’ ORAL EXAMINATION A CASE STUDY AT AN ENGLISH COLLEGE IN YOGYAKARTA - Krisdiyanta, Nugraha (Conscientia - Journal on Language, Literature, and Culture, 2025)
Mistakes are common things in learning of a language. Students make mistakes when learning because of some process such as interlingual transfer in which learners’ L1 influences the process of L2 learning; interlingual transfer where learners sometimes make overgeneralization of a language rule; and the third is the context of learning where sometimes students get false concept since they do not use the real context of communication. This study was taken at a college in Yogyakarta, Indonesia. This paper tries to answer two questions; (1) What kind of error do the students make during their final oral examination? and (2) What are the sources of the error that the students make? By classifying and analyzing the errors, and employing the theory by Taylor and Dulay et al. it is found that the errors are dominated by omission and addition. Those errors are caused by the negative interlingual and intralingual transfers which lead to false concept the students grabs during their learning process. Keywords: mistake, error, interlingual transfer, intralingual transfer